MEMBANDINGKAN RISIKO SISTEMATIS MENGGUNAKAN CAPM-GARCH DAN CAPM-EGARCH - AMELIAH, VIKY; DHARMAWAN, KOMANG; WIDANA, I NYOMAN (E-Jurnal Matematika; Vol 6 No 4 (2017), 2017)
In making stock investments, investors usually pay attention to the rate of return and risk of the stock investment. To calculate risk using capital asset pricing model (CAPM), GARCH, and EGARCH. The data used in this study is secondary data in the form of daily closing price (daily close price), JII price index and monthly SBI rate. All data were processed using matlab 13. The research sample consisted of 6 flagship shares for the period of 2013-2017 ie ADHI, SMGR, UNTR, BSDE, ICBP, KLBF. The conclusion of the research is the beta of each stock including aggressive beta because beta greater than 1. For return CAPM GARACH and CAPM EGARCH obtained Kalbe Farma stock (KLBF) has small beta and big return means GARCH and EGARCH model equally Can predict that stock KLBF shares the least risk and large returns among the six stocks.